2005
DOI: 10.1097/01.coc.0000170582.38634.b6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Breast Reconstruction can Impact Postmastectomy Irradiation

Abstract: Immediate breast reconstruction may impose limitations on the treatment planning of postmastectomy radiotherapy, particularly in regard to providing broad coverage of the chest wall and IMC region while avoiding excess exposure of the heart and lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 49 publications
0
39
0
9
Order By: Relevance
“…Third, some studies have raised the concern that irradiation of the immediately reconstructed breast results in a lower quality of radiation. These studies showed that the majority of radiation plans are unsatisfactory in terms of providing broad coverage of the chest wall and internal mammary nodes while adequately sparing heart and lung [35][36][37]. Fourth, recent studies reported increased tumor recurrence and patient demise when RT was performed following breast reconstruction in comparison with RT delivered before reconstruction [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Third, some studies have raised the concern that irradiation of the immediately reconstructed breast results in a lower quality of radiation. These studies showed that the majority of radiation plans are unsatisfactory in terms of providing broad coverage of the chest wall and internal mammary nodes while adequately sparing heart and lung [35][36][37]. Fourth, recent studies reported increased tumor recurrence and patient demise when RT was performed following breast reconstruction in comparison with RT delivered before reconstruction [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Reconstructions that are subsequently irradiated may have inferior esthetic outcomes and higher complication rates [14]. Also it may pose challenges to optimizing radiotherapy planning and some groups described technical difficulty in delivering PMRT in this subset of patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…The main indication criteria for PMRT are: larger tumor (T3), positive resection margins and positive regional lymph nodes (16). Although the appropriate delivery of radiation to the chest wall following reconstrucion have been sporadically issued (17), the quality of radiotherapy does not seem to be substantially compromised by the presence of reconstructed breast. However, there has been a clear evidence that PMRT increases the surgical complication rate of the reconstruction and worsens its longterm outcomes regardless of the method used (18,19,20).…”
Section: Discussionmentioning
confidence: 99%